A novel change detection method combined with registration for SAR images. Issue 7 (3rd July 2019) - Song, Shengli; Jin, Kan; Zuo, Bin; Yang, Jian
ABSTRACT: In this letter, we propose a novel change detection method combined with image registration. Inspired by the mutual beneficial property of change detection and image registration, we model these two tasks into a unified process and represent this process as an optimization problem. Then, we use the alternating direction method (ADM) algorithm with proper initialization to solve the optimization problem. Finally, we use spatial information to refine the changed component obtained by the ADM algorithm. Experimental results accomplished over synthetic data and RADARSAT-2 synthetic aperture radar (SAR) images demonstrate that the proposed method can improve both the accuracy of image registration and change detection.